Analysis of the Implementation of Midwife Performance Management in Improving Clinical Quality: Study at TPMB (Midwife Independent Practice) Purwakarta Regency, Indonesia - Oktavian, Dyan (Archives of The Medicine and Case Reports, 2024)
Midwife performance management is a systematic and planned process for assessing the performance of midwives in providing midwifery services. Improving clinical quality is the main goal of midwife performance management. This study aims to analyze the implementation of midwife performance management in improving clinical quality at the TPMB (Midwife Independent Practice) Purwakarta Regency, Indonesia. This research uses a qualitative method with a case study approach. The research informants consisted of TPMB management midwives, implementing midwives, and pregnant/maternity women who had utilized TPMB services. Data collection was carried out through in-depth interviews, observation and document review. The research results show that the implementation of midwife performance management in TPMB Purwakarta Regency has been able to improve the clinical quality of midwifery services. This can be seen from the increase in knowledge, skills and attitudes of midwives in providing midwifery services. Midwives have been able to apply midwifery service standards consistently so that they can provide safe, effective, efficient, and quality midwifery services.